2012
DOI: 10.1155/2012/610921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nebulized Morphine on Dyspnea of Mustard Gas-Exposed Patients: A Double-Blind Randomized Clinical Trial Study

Abstract: Background. Dyspnea is one of the main complaints in a group of COPD patients due to exposure to sulfur mustard (SM) and is refractory to conventional therapies. We designed this study to evaluate effectiveness of nebulized morphine in such patients. Materials and Methods. In a double-blind clinical trial study, 40 patients with documented history of exposure to SM were allocated to two groups: group 1 who received 1 mg morphine sulfate diluted by 4 cc normal saline 0.5% using nebulizer once daily for 5 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…This analysis incorporates data from recent studies, (7)(8)(9) including an adequately powered randomized trial, (7) The present study shows that in a pooled analysis of published trials, there is no evidence that opioids affect the submaximal exercise capacity in severe COPD. Any effect of opioids on quality of life remains unclear.…”
Section: What This Study Addsmentioning
confidence: 87%
See 3 more Smart Citations
“…This analysis incorporates data from recent studies, (7)(8)(9) including an adequately powered randomized trial, (7) The present study shows that in a pooled analysis of published trials, there is no evidence that opioids affect the submaximal exercise capacity in severe COPD. Any effect of opioids on quality of life remains unclear.…”
Section: What This Study Addsmentioning
confidence: 87%
“…(7)(8)(9)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) All included studies were randomized and double-blind, and characteristics are shown in Table 1 and 2. One study was a parallel group trial,(9) and 15 were crossover trials.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jensen et al found no differences in the intensity or unpleasantness of perceived dyspnea during cycle ergometry with a single dose of nebulized fentanyl citrate (50 µg) compared with saline in patients with COPD [59]. In contrast, Shohrati et al reported that 1 mg of nebulized morphine given daily for 5 days provided a significant reduction in patient-reported dyspnea on a VAS compared with nebulized normal saline in 40 patients who were thought to develop COPD in part due to inhaling sulfur mustard during military conflict [60].…”
Section: Results Of Rctsmentioning
confidence: 99%